Factors Associated with Exercise among Elderly in Boyolali, Indonesia - Aniek Puspitosari; RB Soemanto; Mahendra Wijaya (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: The elderly will face more problems by getting older. One of which is degenerative disease due to of aging process, such as cardiovascular disease. In the year 2001 (SKRT) data indicated that there were 26.4% elderly suffered from hypertension disease. Exercise for elderly is one of primary preventive actions. Research should be done related to the practice exercise for elderly. This study was aimed to determine the factors of physical exercise for elderly based on health belief model (HBM).Subjects and Method: This was an analytic qualitative study with cross-sectional design. This conducted in Sobokerto, Ngemplak, Boyolali, Central Java, Indonesia. A total sample of 80 elderly with hypertension and participate in physical exercises. Data analysis used chi square and logistic regression.Results: The results showed that the perceived susceptibility, perceived benefits, perceived barriers and cues to action have relationship with physical exercise. There is positive relationship and statically significant between perceived susceptibility with high phycical exercise (OR= 27.01; 95% CI= 2.04 to 357.91; p= 0.012), high perceived benefits (OR= 26.95; 95% CI= 2.20 to 392.05; p= 0.010), high perceived barriers (OR= 0.021; 95% CI= 0.00 to 0.90 p= 0.044), cues to action (OR= 21.37; 95% CI= 1.94 to 259.92; p = 0.044).Conclusion: The HBM constructs on the physical exercise of elderly who are at risk for hypertension. The most important HBM predictors of physical exercise were perceived susceptibility.Keywords: physical exercise, elderly, hypertension, health belief modelCorrespondence: Aniek Puspitosari. Health Polytechnic, Poltekkes of Surakarta Indonesia.Journal of Health Promotion and Behavior (2016), 1(1): 41-45https://doi.org/10.26911/thejhpb.2016.01.01.06